Root extracts of Saussurea costus as prospective detoxifying food additive against sodium nitrite toxicity in male rats. (August 2022) - Elshaer, Samy E.; Hamad, Gamal M.; Hafez, Elsayed E.; Baghdadi, Hoda H.; El-Demerdash, Fatma M.; Simal-Gandara, Jesus
Abstract: The goal of this study was to investigate the effects of three different extracts of Saussurea costus roots (ethanol, methanol, and water) as a food additive in alleviating the harmful effect of sodium nitrite in rat meals. Thirty-five adult male rats were divided into five groups as follows: control, sodium nitrite (NaNO2 ; 75 mg/kg BW, single oral dose), S. costus 70% ethanol, 70% methanol, and aqueous extracts (300 mg/kg BW), respectively for four weeks followed by a single dose of NaNO2 24h before decapitation. Results showed that the 70% ethanol extract of S. costus has a higher concentration of total phenolic content, total flavonoids, and antioxidant effect than the 70% methanol and water extracts. Rats pretreated with S. costus extracts reduced the harmful effects induced by NaNO2 and improved the hematological parameters, liver, and kidney function biomarkers as well as lipid profile as compared to the NaNO2 group. Furthermore, S. costus improved the histopathological alterations in the liver and kidney induced by NaNO2 and improved meat sensory evaluation. Conclusively, the 70% ethanol extract of S. costus roots is the most effective extract as an antioxidant against the toxicity of sodium nitrite in male rats and might be used safely as a natural additive in the food industry. Graphical abstract: Image 1 Highlights: Sodium nitrite induced liver and kidney dysfunction. Sodium nitrite treatment led to histological changes. Saussurea costus roots is rich in antioxidants components. Saussurea costus alleviate the toxic effect of sodium nitrite. Saussurea costus roots ethanol extract improve sensory evaluation of meat.